2014
DOI: 10.1002/mats.201470019
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Macromol. Theory Simul. 7∕2014

Abstract: Cover: A novel hybrid simulation approach combines the deterministic and stochastic modeling of complex polymerization networks, for all types of polymerization reactions in ideal and non‐ideal reactors. The fast deterministic simulation solves the heat and pressure balances and generates position‐dependent event frequency profiles. The detailed stochastic simulation offers insight into the polymeric microstructure of each macromolecule. Further details can be found in the article by E. Neuhaus, T. Herrmann, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…With regard to the hypothesis proposed, it would be quite difficult to demonstrate that none of the previously published sets of kinetic parameters reproduce the observed trends of M n and PD in the multizone autoclave reactor; however, it can be argued that it would suffice to demonstrate that a set of kinetic parameters based on those used by Iedema et al (later called set I parameters) is not capable of reproducing the observed trends in M n , since this set and the one by Krallis et al are the only two parameter sets that predict realistic values of PD, and both works use very similar parameter values (largely based on those of Pladis and Kiparissides except for the scission reaction). Other recent stochastic models also predict broad MWDs for LDPE tank reactors, but they do not report PD values . Other recent works that also resort to stochastic models report similar results for tubular reactors …”
Section: Resultsmentioning
confidence: 86%
“…With regard to the hypothesis proposed, it would be quite difficult to demonstrate that none of the previously published sets of kinetic parameters reproduce the observed trends of M n and PD in the multizone autoclave reactor; however, it can be argued that it would suffice to demonstrate that a set of kinetic parameters based on those used by Iedema et al (later called set I parameters) is not capable of reproducing the observed trends in M n , since this set and the one by Krallis et al are the only two parameter sets that predict realistic values of PD, and both works use very similar parameter values (largely based on those of Pladis and Kiparissides except for the scission reaction). Other recent stochastic models also predict broad MWDs for LDPE tank reactors, but they do not report PD values . Other recent works that also resort to stochastic models report similar results for tubular reactors …”
Section: Resultsmentioning
confidence: 86%
“…It is an individual macromolecule approach, which calculates topologies of an ensemble of macromolecules one after the other depending only on reaction conditions as implemented in the kinetic model. [10] A reaction frequency R i is calculated for each reaction i of the network by the deterministic model. The reaction frequency is defined as the corresponding reaction rate divided by considered moment of the respective polymeric species.…”
Section: Multiscale Modelingmentioning
confidence: 99%
“…Furthermore, the presented approaches are either suitable for modeling autoclave or tubular reactors. Therefore Neuhaus et al [13,14] developed a coupled deterministic and stochastic simulation approach to model the polymeric microstructure independent of the reactor type. Eckes [15,16] extended that model and validated it for homopolymerizations of ethene in autoclaves.…”
Section: Literature Reviewmentioning
confidence: 99%